Self-Ascribed Paranormal Ability: Reflexive Thematic Analysis - Drinkwater, Kenneth Graham; Dagnall, Neil; Walsh, Stephen; Sproson, Lisa; Peverell, Matthew; Denovan, Andrew (Frontiers in Psychology, 2022)
This study investigated personal perceptions (involvements) and comprehensions (interpretations) of self-ascribed paranormal facilities. Twelve participants with alleged supernatural powers took part in semi-structured interviews exploring their professed abilities and experiences. These examined the origin, phenomenology, and nature of individual facilities. Interview transcripts were analysed using reflexive thematic analysis (RTA), a qualitative method that identifies patterns within data. Four major themes emerged: Formative Influences (sub-themes: Gifted family members and anomalous occurrence), Subjective paranormal experience (sub-themes: Transcendental/mystic, communication with deceased/spirits, and extra-sensory perception/ESP), Processes (sub-themes: Mediation and Channeling, and Control) and Perception of Reality (sub-themes: Self-awareness and fantastic/surreal perceptions). Consideration of themes revealed an inextricable link between perception, interpretation, and faith in ability. Within narratives, interviewees outlined and established the validity of their powers. Explicitly, they drew upon supporting evidence and discounted conventional explanations. Generally, accounts reflected individual attempts to rationalize and understand self-ascribed paranormal abilities. The authors discuss these processes and suggest ways in which to extend and develop subsequent research.